Implementation of the Scaffolding Approach to Improve Student Learning Outcomes in Islamic Education Learning at SMP Negeri 1 Kolang - Nasution, Yusnita; Lubis, Saida Sopa; Dirmaya, Eva; Hidayati, Sri; Fatimah, Siti (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to analyze the application of scaffolding material in improving Islamic Religious Education (PAI) learning outcomes on the material Believing in the Prophets and Messengers of Allah, and how the application can shape the character of a digital generation with noble morals among grade 8 students of UPTD SMP Negeri 1 Kolang, Kolang District, Central Tapanuli Regency. Scaffolding is a learning approach that provides gradual guidance to students according to their level of understanding, so that they can achieve independence in learning. The research method used is a qualitative method with a descriptive approach, where data is collected through observation, interviews, and documentation. The results of the study showed that the application of scaffolding strategies in PAI learning significantly improved students' understanding of the material Believing in the Prophets and Messengers of Allah. Students become more active in the learning process, are able to think critically, and better understand and internalize the values ​​of Islamic teachings in everyday life. In addition, the use of scaffolding also helps students face the challenges of the digital era by forming characters based on Islamic values, such as honesty, responsibility, and mutual respect. Thus, this strategy is an effective solution in improving the quality of Islamic Religious Education learning and forming the character of a digital generation with morals.